Hubungan Pemahaman Ilmu Tajwid dengan Kemampuan Membaca Al-Qur’an Siswa SMP - Endang Amalia; Wirdati Wirdati (AS-SABIQUN, 2022)
The holy book of Muslims which was revelaed to Rasulullah SAW. The Qur’an is used as a guide for Muslims in managing and carrying out life in this worl and in the hereafter. The science of recitation is the science used to read the Qur’an properly and correctly. The formulation of the problem in this research is “is there a significant relationship between the understanding of recitation and the ability to read the Qut’an of the student of SMPNegeri 15 Padang?”. This study aims to setermine the understanding of the science of recitation of SMP student, to determine the ability to read the Qr’an of SMPNegeri 15 Padang. This research uses correlational qyantitative research. The population in this random sampling teschnique. The sample in this study wa 87 students. The results of the study. Based on research obtained through the written test method to obtain data on variable X, namely the understanding of the science of recitation is in the good category as evidenced by 45% of students in the strong category. And the oral test method to abtain Y variable data, namely the ability to tead the Qur’an of the students of SMP Negeri 15 Padang in the good category as evidenced by 45 % of the students in the strong category. And there is a relationship between the understanding og recitation and the ability to read the Qur’an SMP students with an R Square test of 0,498 (49.8%) which shows that the dependent variable,.